Active and passive synergistic antibacterial and healing-promoting dressing as well as preparation method and application thereof

Through the composite technology of dopamine, sodium alginate and zinc ions, active and passive collaborative antibacterial and healing dressings are constructed, which solves the problems of high cytotoxicity and limited antibacterial effects of existing antibacterial dressings, and achieves the effect of efficient antibacterial and promoting wound healing.

CN119950792AActive Publication Date: 2025-05-09QINGDAO UNIV +2
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202510062452.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-05-09
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

In actual use, existing antibacterial wound dressings have problems such as high cytotoxicity, limited antibacterial effect, and short-lasting efficacy, making it difficult to effectively prevent and control burn wound infection and promote healing.

Method used

Active passive synergistic antibacterial and healing dressing constructed by dopamine, sodium alginate and zinc ions is used to form a composite dressing with efficient antibacterial, absorbing leucorrhea and promoting healing through the crosslinking technology of dopamine-modified polyurethane sponge and sodium alginate and zinc ions.

Benefits of technology

It has achieved efficient antibacterial effect, with a bacterial resistance rate of 80±1.2%, and an active and passive collaborative antibacterial rate of more than 99%, which has significantly improved the anti-infection ability, promoted wound healing, and improved the quality of life of patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119950792A_ABST
    Figure CN119950792A_ABST
Patent Text Reader

Abstract

The invention discloses an active and passive synergistic antibacterial and healing-promoting dressing as well as a preparation method and application thereof, and belongs to the technical field of burn dressings. According to the technical scheme, the dressing is a dopamine-sodium alginate-zinc ion composite functional dressing based on a short-period and cyclic cross-linked coating technology. The preparation method comprises the following steps: 1) compounding dopamine and polyurethane sponge; (2) sodium alginate-zinc ions are subjected to short-period, cyclic and repeated cross-linking, and a gelation coating is formed; and (3) drying the crosslinked dressing, so as to obtain the active and passive synergistic antibacterial and healing-promoting dressing. The active and passive synergistic antibacterial dressing is prepared through a short-time multi-cycle cross-linking technology, the efficient antibacterial effect integrating active and passive antibacterial principles is achieved, meanwhile, the multiple functions of absorbing seepage and promoting healing are achieved, and the active and passive synergistic antibacterial dressing is suitable for production and application of dressing related to open wounds such as burns and scalds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of open wound dressings for burns, scalds, etc., and specifically relates to an active and passive synergistic antibacterial and healing-promoting dressing, and a preparation method and application thereof. Background Art

[0002] Burns and scalds refer to skin tissue damage caused by heat, electric current, chemicals, lasers, radiation, etc., and are common accidental injuries in life and production. If the wound at the burn site is not properly treated, it can be life-threatening. At present, wound infection is one of the main causes of death in burn patients. In clinical work, wound dressing change is one of the most effective ways to control infection. The traditional method is to use gauze combined with various antibacterial drugs for dressing change. As the most common medical dressing, the advantages of gauze are protection of the wound, good absorbability, wide source, simple production, and low price. However, the disadvantages are also prominent: it cannot keep the wound moist, hinders the epithelialization of tissue cells, delays wound healing, affects healing, and easily causes pain when changing dressings. It is also difficult to fully drain the exudate from the infected wound, which easily leads to accumulation of exudate and aggravates local infection.

[0003] Infection is the most common complication after burns. The skin is the main barrier against pathogens in the environment. Burns and scalds destroy the integrity of the skin. The invasion of infection sources (mainly bacteria, but also yeast, fungi and viruses) leads to skin tissue and systemic infection. In severe cases, sepsis occurs, which becomes the main cause of death in burn patients. Due to the diversity of infection and the changes in drug resistance of pathogens, antibiotic treatment faces challenges such as limited efficacy and abuse. Therefore, there is an urgent need for new anti-infection wound dressings and their potential is huge.

[0004] In recent years, composite materials combining active and passive antibacterial strategies have gradually become a research hotspot and have been reported in fields such as environmental science, but active and passive synergistic antibacterial dressings for skin wounds have not been reported. Existing antibacterial wound dressing technologies are mainly divided into two categories: active bactericidal strategies (such as silver ions, antibiotics, etc.) and passive antibacterial strategies (such as polymer surface modification to form physical antibacterial); metal ions can provide good antibacterial effects, and commonly used antibacterial ions are silver ions, but they have shortcomings such as high cytotoxicity, high cost, and limited clinical application. Chinese invention patent CN109010898A discloses a chitosan-based gauze dressing loaded with metal ions. The metal ions loaded on the gauze dressing can be added with one or more metal ions as needed, and can be directly applied to the wound surface or applied by stacking layers. The concentration of loaded metal ions can be adjusted by changing the concentration of the prepared metal ion solution; Chinese invention patent CN114456437A discloses a polydopamine coating modified antibacterial polyurethane dressing and its preparation method and application, the preparation method comprising the following steps: dopamine, sulfobetaine methacrylate, H2O2 and CuSO4 are added to a Tris solution in sequence, and a co-deposition solution is obtained after mixing evenly; the sponge substrate is immersed in the co-deposition solution for shaking treatment, and is taken out and dried to constant weight to obtain a polydopamine coating modified antibacterial polyurethane dressing. The co-deposition reaction of dopamine and sulfobetaine methacrylate is induced by CuSO4 / H2O2, and the polyurethane sponge is co-deposited and modified, so that the prepared polyurethane dressing exhibits broad-spectrum, long-lasting and stable antibacterial properties. However, dressings with a single antibacterial strategy have certain limitations in practical applications, such as excessive cytotoxicity, limited antibacterial effect, and unsustainable efficacy. Therefore, how to develop a wound dressing with active and passive antibacterial properties is a problem that those skilled in the art need to solve urgently. Summary of the invention

[0005] The present invention provides an active and passive synergistic antibacterial and healing-promoting dressing and its preparation method and application. The composite functional dressing with active and passive synergistic antibacterial strategy can effectively prevent and control burn wound infection and promote healing. The dressing uses dopamine (DOP), sodium alginate (SA) and zinc ions (Zn 2+ ) is constructed, through active and passive synergistic antibacterial mechanisms and short-term multiple cross-linking technology, it realizes multiple functions such as high-efficiency antibacterial, absorption of exudate and promotion of healing. It is suitable for the production of dressings related to open wounds such as burns and scalds.

[0006] The technical solution of the present invention is:

[0007] In the first aspect, an active and passive synergistic antibacterial and healing-promoting dressing is disclosed, wherein the dressing is a dopamine-sodium alginate-zinc ion composite functional dressing, and the dressing is a modified hydrogel-coated polyurethane dressing synthesized by modifying dopamine and then cross-linking with sodium alginate and zinc ions.

[0008] Preferably, the dressing has excellent passive adhesion and antibacterial properties and active antibacterial properties of zinc ion release; the passive antibacterial efficiency can reach 80±1.2%, and the antibacterial rate of the active and passive synergistic antibacterial wound dressing can reach more than 99%.

[0009] Preferably, the dressing has good mechanical properties and liquid management capabilities. The liquid absorption rate of the dressing is more than twice that of traditional polyurethane sponge PU, and it has excellent water absorption and water retention properties, and can effectively control wound exudate.

[0010] Preferably, the dressing uses a polyurethane sponge as a substrate, and forms a passive antibacterial layer with hydrophilicity and good water absorption through in-situ polymerization of dopamine and the polyurethane sponge; then, sodium alginate and zinc ion solution are used for short-cycle, cyclic cross-linking treatment to form a hydrogel coating containing zinc ions, thereby obtaining a modified polyurethane dressing.

[0011] In a second aspect, a method for preparing the active and passive synergistic antibacterial and healing-promoting dressing is disclosed, comprising the following steps:

[0012] 1) Composite of dopamine and polyurethane sponge: The polyurethane sponge is mixed with the dopamine solution and self-polymerized in an alkaline environment to form a polydopamine coating;

[0013] 2) Sodium alginate-zinc ion gelation: The dopamine-modified polyurethane sponge is immersed in a sodium alginate and zinc ion solution, and is cross-linked multiple times for a short time to form a zinc-containing sodium alginate hydrogel coating;

[0014] 3) freeze-drying the cross-linked dressing to obtain the active and passive synergistic antibacterial and healing-promoting dressing.

[0015] Preferably, the concentration of the dopamine solution in step 1) is 2±0.5 mg / mL, and the alkaline environment in step 1) is a tris-hydroxymethylaminomethane hydrochloride (Tris-HCl) buffer.

[0016] Preferably, in step 2), the concentration of sodium alginate is 0.01-2 g / mL, and the concentration of zinc ions is 8-40 mg / mL.

[0017] Preferably, the time of short-term multiple cross-linking in step 2) is 0.5-3 min, and the number of cross-linking is 2-6 times.

[0018] In a third aspect, the application of the active and passive synergistic antibacterial and healing-promoting dressing in the preparation of dressings related to open wounds is disclosed.

[0019] Alginate, especially sodium alginate, is a natural polymer with negative charge characteristics. The carboxyl group (-COO -) can form ionic bonds with metal ions, thereby building a network structure and promoting the formation of gel. 2+ ) plays a vital role. Zinc ions not only interact with the carboxyl groups of alginate to form a stable complex, but also significantly improve the mechanical properties and stability of the gel due to their selective effect.

[0020] Instantaneous multiple cross-linking technology: Different from the traditional method of curing into gel after a one-time cross-linking reaction, instantaneous multiple cross-linking refers to the use of instantaneous multiple technology to introduce zinc ions during the gel formation process, aiming to enhance the cross-linking density of the gel network, thereby constructing a more stable three-dimensional network structure. Precise control can be achieved by flexibly adjusting the concentration of zinc ions or the reaction time.

[0021] Instantaneous multiple cross-linking has the following advantages:

[0022] Improve gel strength: Instantaneous multiple cross-linking can enhance the structural stability of the gel and improve the mechanical strength of the gel, enabling it to withstand more stress and adapt to different application requirements.

[0023] Controllability: By adjusting the number of cross-linking and reaction conditions, the structure and properties of the gel, such as swelling, mechanical strength and sustained release ability, can be precisely controlled.

[0024] Improved metal ion release rate: Due to the increase in cross-linking density, the pore structure of the gel is more uniform and the zinc ion release rate can be effectively controlled, thereby improving the bioavailability and efficacy of the antimicrobial factors.

[0025] Improved stability: Multiple cross-linking enhances the network structure of the gel and maintains the integrity of the sponge pores after freeze-drying. It reduces the degradation rate of the gel during use and prolongs its use time in vivo and in vitro.

[0026] Active and passive synergistic antibacterial mechanism: Dopamine forms a polydopamine (PDA) coating through self-polymerization, forming a physical barrier on the wound surface, adhering bacteria to the sponge, preventing bacterial invasion, and playing a passive antibacterial role; while zinc ions exert antibacterial effects through an active release mechanism, which can effectively kill bacteria. The synergistic effect of the two significantly enhances the antibacterial ability of the dressing.

[0027] Promote wound healing: The dressing has strong antibacterial properties and the ability to effectively absorb wound exudate, combined with healing factors to increase the wound healing rate. In addition, the dressing also has the advantages of promoting collagen deposition and reducing inflammatory infiltration.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The dressing prepared by the present invention has high-efficiency antibacterial properties. Through dopamine modification and compounding with sodium alginate and zinc ions, a dressing with active and passive synergistic antibacterial mechanisms has been successfully constructed. The polydopamine coating formed by dopamine can form a physical barrier on the wound surface, effectively adhere to and prevent bacterial invasion, and the active release of zinc ions further enhances the antibacterial effect. Experiments have shown that the antibacterial rate of the dressing against Staphylococcus aureus (S.aureus) and Escherichia coli (E.coli) exceeds 99%, and can continue to sterilize for 11 days and 9 days, significantly improving the anti-infection ability, and has a bacteriostatic ability of 80% ± 1.2%, achieving both short-term blocking and long-term sterilization protection.

[0030] 2. The dressing of the present invention uses polyurethane sponge as a substrate, and forms a passive antibacterial layer with hydrophilicity and good water absorption through in-situ polymerization of dopamine and polyurethane sponge. The preparation method of the present invention uses instantaneous multiple cross-linking treatment of sodium alginate and zinc ions to form a hydrogel coating containing zinc ions. The dressing has high porosity, good mechanical properties and excellent elasticity, and is suitable for long-term use in the treatment of burn wounds.

[0031] 3. The dressing of the present invention has excellent liquid management capabilities, and its liquid absorption rate is twice that of traditional polyurethane (PU). It also has good water retention properties and can effectively control wound exudate, providing a drier and cleaner healing environment for the wound.

[0032] 4. The dressing of the present invention also has a significant effect in promoting wound healing. In a rat scald model, dopamine-zinc alginate dressing can accelerate the wound healing process, increase the wound healing rate by 27.5%, and perform well in promoting microangiogenesis, collagen deposition and inflammation control. Its strong antibacterial ability can reduce wound infection and provide strong protection for wound healing. At the same time, the dressing can also effectively absorb wound exudate, reduce wound burden, promote collagen deposition and reduce the degree of inflammatory infiltration, thereby accelerating the wound healing process.

[0033] 5. The dressing preparation method of the present invention is simple and easy to operate, and the required raw materials are widely available and low in cost. Through the steps of compounding dopamine with polyurethane sponge, gelation of sodium alginate-zinc ions, and freeze-drying treatment, an active and passive synergistic antibacterial and healing-promoting dressing with excellent performance can be prepared, which provides strong support for the wide application and industrialization of the dressing.

[0034] 6. The active and passive synergistic antibacterial and healing-promoting dressing provided by the present invention is suitable for open wounds such as burns and scalds, and can not only effectively prevent and control wound infection, but also promote wound healing and improve the quality of life of patients. At the same time, its preparation method is simple and easy to promote, and has high practical application value and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a surface morphology of the polyurethane (PU) of the present invention, the dopamine-zinc alginate blended sponge (APBM-L) prepared in Comparative Example 3, and the dopamine-zinc alginate dressing (APBM) prepared in Example 1.

[0036] Figure 2 It is a Fourier transform infrared spectrum (FTIR) test chart of the active and passive synergistic antibacterial and healing promoting dressing (APBM) prepared in Example 1 of the present invention, polyurethane (PU), DPU prepared in Comparative Example 1, and ZnPU prepared in Comparative Example 2.

[0037] Figure 3 This is a graph showing the water absorption results of the polyurethane sponge PU of the present invention and the APBM dressing prepared in Example 1.

[0038] Figure 4 It is a graph showing the water retention rate measurement results of the polyurethane sponge PU of the present invention, the APBM prepared in Example 1, and the APBM-L prepared in Comparative Example 3.

[0039] Figure 5 This is a graph showing the results of measuring the transmittance and porosity of the active and passive synergistic antibacterial and healing-promoting dressing (APBM) and PU prepared in Example 1 of the present invention.

[0040] Figure 6 It is a graph of stress-strain test of dopamine-zinc alginate dressing APBM and PU prepared in Example 1 of the present invention.

[0041] Figure 7 It is a result diagram of in vitro antibacterial performance test of PU of the present invention, DPU prepared in comparative example 1, ZnPU prepared in comparative example 2, and APBM prepared in example 1.

[0042] Figure 8 It is a graph showing the results of the bacterial ring experiment of the dressing PU of the present invention, the DPU prepared in comparative example 1, the ZnPU prepared in comparative example 2, and the APBM prepared in example 1.

[0043] Fig. 9 It is a graph showing the antibacterial test results of the PU of the present invention, the DPU prepared in Comparative Example 1, the ZnPU prepared in Comparative Example 2, and the APBM prepared in Example 1.

[0044] Fig.10 This is a graph showing the results of the biosafety test (cytotoxicity, hemolysis) of the dressing prepared in Example 1 of the present invention.

[0045] Fig.11 It is a comparison chart of the wound healing effects of APBM prepared in Example 1 of the present invention, and DPU and PU prepared in Comparative Example 1 in a rat burn and scald model.

[0046] Fig.12 It is a comparative chart of histological index analysis of APBM prepared in Example 1 of the present invention, DPU and PU dressings prepared in Comparative Example 1 in a rat burn and scald model.

[0047] Fig.13 This is a surface morphology image of the dressing prepared in Comparative Example 4 of the present invention.

[0048] Fig.14 This is a surface morphology image of the dressing prepared in Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0049] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0050] Example 1

[0051] The preparation method of the active and passive synergistic antibacterial and healing-promoting dressing comprises the following steps:

[0052] 1) Composite of dopamine and polyurethane sponge: Cut the medical polyurethane sponge PU into a cylinder with a diameter of 10mm and a height of 5mm, wash and dry it, and sterilize it with ultraviolet light. At the same time, prepare Tris-HCl buffer (10mmol / L, pH=8.5). Add 2mg of dopamine hydrochloride (Dop-HCl) powder to the Tris-HCl buffer to maintain the concentration of dopamine hydrochloride at 2mg / mL. After dissolution, put the dry sponge into a wide-mouth bottle and place it in a shaking table at 37°C to react for 12 hours, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and freeze-dry to obtain a polyurethane sponge (DPU) with a polydopamine (PDA) coating.

[0053] 2) Sodium alginate-zinc ion gelation:

[0054] A. Immerse the polydopamine-coated sponge (DPU) in a sodium alginate solution (0.01 g / mL, viscosity 80 mPa·s) for 5 minutes, and gently squeeze out the residual sodium alginate on the surface of the sponge;

[0055] B. After immersing in zinc chloride solution (12 mg / mL) for 10 seconds, immerse in prepared sodium alginate solution (0.01 g / mL, viscosity 80 mPa·s) and let stand for 10 seconds;

[0056] C. After repeating step B) three times, finally add zinc chloride solution (12 mg / mL) and place in a shaker at 37°C for reaction for 2 hours. After freeze-drying, it becomes dopamine-zinc alginate dressing, i.e. active-passive synergistic antibacterial and healing-promoting dressing, hereinafter referred to as (APBM).

[0057] This embodiment performs short-term multiple cross-linking to form a zinc-containing sodium alginate hydrogel coating, which not only provides active antibacterial effects but also optimizes the water absorption and flexibility of the dressing.

[0058] Example 2

[0059] The preparation method of the active and passive synergistic antibacterial and healing-promoting dressing comprises the following steps:

[0060] 1) Composite of dopamine and polyurethane sponge: Cut the medical polyurethane sponge PU into a cylinder with a diameter of 10mm and a height of 5mm, wash and dry it, and sterilize it with ultraviolet light. At the same time, prepare Tris-HCl buffer (10mmol / L, pH=8.5). Add 1.5mg of dopamine hydrochloride (Dop-HCl) powder to the Tris-HCl buffer to maintain the concentration of dopamine hydrochloride at 1.5mg / mL. After dissolution, put the dry sponge into a wide-mouth bottle and place it in a shaking table at 37°C to react for 12 hours, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and freeze-dry to obtain a sponge (DPU) with a polydopamine coating.

[0061] 2) Sodium alginate-zinc ion gelation:

[0062] A. Immerse the polydopamine-coated sponge (DPU) in a sodium alginate solution (0.01 g / mL, viscosity 80 mPa·s) for 5 minutes, and gently squeeze out the residual sodium alginate on the surface of the sponge;

[0063] B. After immersing in zinc chloride solution (20 mg / mL) for 10 seconds, immerse in prepared sodium alginate solution (0.01 g / mL, viscosity 80 mPa·s) and let stand for 10 seconds;

[0064] C. After repeating step B) three times, finally put in zinc chloride solution (12 mg / mL) and place in a 37°C shaker for reaction for 2 hours. After freeze-drying, a dopamine-zinc alginate sponge is obtained, namely the active and passive synergistic antibacterial and healing-promoting dressing.

[0065] Comparative Example 1

[0066] The preparation method of the passive antibacterial dressing polydopamine coated sponge (DPU) is as follows: cut the medical polyurethane sponge PU into a cylinder with a diameter of 10 mm and a height of 5 mm, wash and dry it, and sterilize it with ultraviolet light. At the same time, prepare Tris-HCl buffer (10 mmol / L, pH=8.5). Add 2 mg of dopamine hydrochloride (Dop-HCl) powder to the Tris-HCl buffer to maintain the concentration of dopamine hydrochloride at 2 mg / mL. After dissolution, put the dry sponge into a wide-mouth bottle and place it in a shaking table at 37°C to react for 12 hours, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and freeze-dry it to obtain a sponge (DPU) with a polydopamine coating.

[0067] Comparative Example 2

[0068] The preparation method of active antibacterial dressing zinc polyurethane sponge (ZnPU) is as follows: medical polyurethane sponge PU is cut into cylinders with a diameter of 10 mm and a height of 5 mm, cleaned and dried, sterilized by ultraviolet light, immersed in zinc chloride solution (12 mg / mL), placed in a shaker at 37°C for reaction for 3 hours, washed three times with deionized water, and frozen and dried to obtain zinc polyurethane sponge ZnPU.

[0069] Comparative Example 3

[0070] Dopamine-zinc alginate blended sponge (APBM-L) was prepared by a blending method. The DPU prepared in Comparative Example 1 was first immersed in a zinc ion solution (12 mg / mL) for 30 seconds and then directly added with a sodium alginate solution (0.01 g / mL). The mixture was placed in a shaker at 37°C for reaction for 2 hours and freeze-dried to obtain APBM-L.

[0071] Comparative Example 4

[0072] The difference from Example 1 is that in step 2), step B is to immerse the dressing in a zinc chloride solution (12 mg / mL) for 20 seconds and then immerse it in the prepared sodium alginate solution for 20 seconds; the rest is the same as Example 1, and the surface morphology of the prepared dressing is as follows: Fig.13 As shown, the open-pore structure inside the dressing sponge showed a gelled wrinkled state with unclear layers.

[0073] Comparative Example 5

[0074] The difference from Example 1 is that in step 2), "repeat step B) three times" in step C is changed to "repeat step B) once". The rest is the same as Example 1. The surface morphology of the prepared dressing is as follows: Fig.14 As shown, the morphology and structural integrity of the sponge were not affected and exhibited open cell structure and soft foam characteristics similar to those of the base sponge.

[0075] The active and passive synergistic antibacterial and healing-promoting dressing prepared in Example 1 and the dressing prepared in the comparative example were subjected to physical and chemical property characterization and biological performance testing, as follows:

[0076] The surface morphology of polyurethane (PU) and dopamine-zinc alginate blended sponge (APBM-L) prepared in comparative example 3 and dopamine-zinc alginate dressing (APBM) prepared in example 1 were observed by scanning electron microscope (SEM) at three different magnifications. Scanning electron microscope (SEM, JSM-6390LV, JEOL) was used to observe the pore structure changes of the material to confirm the coating uniformity and porous structure integrity. The surface and cross-sectional morphology were observed using SEM. The sponge sample was observed at a voltage of 15 kV after 160 seconds of gold coating. The results are shown in Figure 2. Figure 1 As shown. The cross-sectional surface of the PU sponge is very smooth, without impurities and sedimentary substances. The deposition of self-polymerized polydopamine (PDA) particles was observed on the surface of the dopamine-zinc alginate blended sponge (APBM-L), indicating that PDA successfully adhered to the PU surface. In the SEM image of the dopamine-zinc alginate dressing (APBM), it can be seen that a gelled wrinkled state appeared on the sponge skeleton, forming a rough surface structure, but the morphology and structural integrity were not affected at all, and it showed good open-pore structure and soft foam characteristics, and the pore size distribution was relatively concentrated. The porous structure was not destroyed in the dopamine-zinc alginate dressing (APBM). However, the dopamine-zinc alginate blended sponge (APBM-L) synthesized by long-term blending was severely gelled, and the internal open-pore structure had been destroyed, becoming loose and unclear.

[0077] The active and passive synergistic antibacterial and healing-promoting dressing (APBM), polyurethane (PU) prepared in Example 1, DPU prepared in Comparative Example 1, and ZnPU prepared in Comparative Example 2 were tested by Fourier transform infrared spectroscopy (FTIR). The results are as follows: Figure 2 As shown in the figure, the successful introduction of zinc ions and sodium alginate was verified. The spectrum of DPU is similar to that of PU, with a wavelength of 3314 cm -1 One peak becomes stronger, which is the stretching vibration of the -OH group of the coated polydopamine, proving that PDA is successfully coated on the PU surface. -1 There is a broad hydroxyl absorption peak at the position of the 2-hydroxyl group, and the peaks of asymmetric and symmetric stretching vibrations are about 1618 cm -1 and 1419cm -1 The result is due to its carboxylate ion state. 2+ Hydrogels are prepared by cross-linking. The hydroxyl or carboxyl groups of the alginate SA molecular chain and Zn 2+ The active hydrogen absorption peaks, such as hydroxyl, amino and carboxyl groups, are at 3000-3500cm -1In addition, due to the carboxylate anion and Zn 2+ The strong interaction between the carbonyl stretching vibration absorption peak (COO-) from 1618cm -1 Displacement and 1419cm -1 Up to 1624cm -1 and 1502cm -1 .

[0078] The water absorption and water retention capacity of wound dressings is an important characteristic for evaluating the effect of wound exudate cleaning and moisturizing. An ideal wound dressing should maintain wound moisturization while effectively preventing excessive exudate from accumulating on the wound surface.

[0079] The water absorption of the polyurethane sponge PU and the APBM dressing prepared in Example 1 was measured, and the water absorption can be evaluated according to the YY / T0471.1-2004 method. The dry sample for measurement was weighed in triplicate, then immersed in phosphate buffered saline (PBS, pH = 7.4), and finally placed in an oven at 37°C for 10 minutes. After standing for 30 seconds, the sample taken out with tweezers was weighed until the droplet formation stopped, and the water absorption capacity of the sponge was calculated according to the formula.

[0080]

[0081] Where: m1-initial mass of sponge, g; m2-mass of sponge after absorbing water, g; test results are as follows Figure 3 shown.

[0082] The water retention rate of the polyurethane sponge PU, the APBM prepared in Example 1, and the APBM-L prepared in Comparative Example 3 was measured. The specific test method was: the dressings were placed in pure water, and after the water absorption reached saturation, the samples were taken out at different time points, and the excess liquid on the surface was wiped off and weighed. The calculation formula is as follows:

[0083]

[0084] Where: W2-mass of the sponge that has reached saturation state, g;

[0085] W1-mass of sponge after being placed for different time, g; test results are as follows Figure 4 shown.

[0086] Due to the hydrophilic modification, the water absorption and water retention capacity of dopamine-zinc alginate dressing APBM and APBM-L have been improved. Compared with polyurethane sponge PU, dopamine-zinc alginate dressing APBM can absorb liquid to a high water absorption of 1704% and a water retention rate of 54% within 10 minutes. It is enough to make the wound dressing absorb wound exudate while keeping the wound surface moist.

[0087] An ideal wound dressing should maintain wound moisturization while effectively preventing excessive exudate from accumulating on the wound surface. A certain degree of moisture and gas permeability through the wound dressing is important to prevent excessive wound dehydration and exudate accumulation. Therefore, an appropriate water vapor transmission rate (WVTR) is also particularly important. The ideal WVTR is 2000–2500 g·m -2 / day. The active and passive synergistic antibacterial and healing-promoting dressing (APBM) and polyurethane sponge PU prepared in Example 1 were tested for permeability. The specific test method is: the water vapor permeability (WVTR) of the dressing is measured according to YY / T0471.2-2004. In short, first add a certain amount of pure water to the centrifuge tube, cut the sponge dressing APBM prepared in Example 1 into uniform shapes and place them at the mouth of the centrifuge tube, and then place the device in a constant temperature box at 37°C. After different time periods, take it out and measure its volume change. The specific formula is as follows:

[0088]

[0089] Where: m0-initial mass of the centrifuge tube containing sponge and water, g;

[0090] m t -The mass of the entire device after time t, g;

[0091] S-the area of ​​the centrifuge tube orifice, mm;

[0092] t-the number of days the entire device is placed in a constant temperature incubator, d; the test results are as follows Figure 5 shown.

[0093] Dopamine-zinc alginate dressing and polyurethane sponge PU dressing (2450.9 g·m -2 ·day -1 ) can be reduced by 18.17%. -2 ·day -1 ) can reduce water loss by 82.35% compared to traditional cotton, with an ideal permeability value. This not only helps create a humid environment, but also prevents excessive dehydration.

[0094] Porosity is an important parameter for the application of medical sponges. Highly porous structures not only have a high specific surface area, but also help to absorb exudates. The liquid volume displacement method was used to measure the porosity of the active and passive synergistic antibacterial and healing dressing (APBM) and the polyurethane sponge PU prepared in Example 1. The specific test method is: weigh the samples separately and measure and calculate their volumes (cylindrical, with a radius r of approximately 1.1 cm and a thickness h of approximately 0.5 cm), weigh their masses, record them as W1, and put them in anhydrous ethanol and soak them for 5 minutes to allow them to fully absorb anhydrous ethanol. Then take the sponge sample out of the anhydrous ethanol, gently absorb and wipe off the excess anhydrous ethanol, and immediately weigh and record the mass W2. The sample porosity is calculated using the following formula:

[0095]

[0096] Where W1 and W2 are the initial weight and final weighing weight of the sponge sample, respectively. The porosity was calculated based on three parallel sample tests and expressed as the arithmetic mean and standard deviation (M±SD, n=3).

[0097] Compared with the porosity of PU (81%), the porosity of dopamine-zinc alginate dressing sponge can reach 86.7%. After dopamine DOP and gelation modification, the porosity of dopamine-zinc alginate dressing composite dressing increases. Figure 1 The SEM image of the composite sponge dopamine-zinc alginate dressing shows a fairly regular and homogeneous high porosity structure, which makes it a potential application prospect in wound dressing.

[0098] The dopamine-zinc alginate dressing APBM and polyurethane sponge PU prepared in Example 1 were subjected to stress-strain tests to test the stiffness of the dressing. The specific test method was as follows: the mechanical properties of the dressing were evaluated by a universal testing machine (WDW-05L, China) in accordance with GB / T6344-2008 and GB / T33609-2017. Standard rectangular specimens (10cm×1.5cm×0.5cm, under dry conditions) were tested at a tensile rate of 100mm / min. Compression tests were performed at a constant speed of 5mm / min. The experiments were conducted at room temperature. The test was repeated at least 3 times for each specimen. The test results are as follows: Figure 6As shown. The tensile strengths of polyurethane sponge PU and dopamine-zinc alginate dressing APBM are 137.3MPa and 238.67MPa, respectively, while the corresponding fracture strains are 479.99% and 669.01%, respectively. After the introduction of polydopamine PDA oxidative polymerization and zinc alginate multilayer coating, the mechanical properties of PU sponge are significantly improved. Compared with PU, the tensile strength of dopamine-zinc alginate dressing is increased by 101.37kPa and the elongation at break is increased by 189.02%. The compression test results show that the compressive strength of dopamine-zinc alginate dressing is 28.4kPa, which is 11.1kPa higher than that of PU. The mechanical properties are improved and the flexibility of PU is enhanced due to the addition of sodium alginate gel.

[0099] The in vitro antibacterial performance of PU, DPU prepared in comparative example 1, ZnPU prepared in comparative example 2, and APBM prepared in Example 1 was tested. The specific test method was as follows: colony counting method, using a culture medium with only Staphylococcus aureus, Escherichia coli, and Candida albicans added as a control group, and evaluating the antibacterial activity of the dressing against Escherichia coli, Staphylococcus aureus, and fungi. The sponge was cut into a cylinder with a height of 5 mm and a diameter of 20 mm, and sterilized by ultraviolet for 30 minutes. 4 mL of phosphate buffered saline (PBS) was added to the sterilized sponge for full soaking, and then 200 uL of three bacterial solutions (10 6 CFU / mL) at 37℃ for 2h. After incubation, dilute the bacterial solution and apply 100uL of bacterial solution on the agar plate. After incubation at 37℃ for 24h (the fungal culture medium is placed at 30℃), observe the colonies on the agar plate and take pictures. The test results are as follows Figure 7 shown.

[0100] Compared with the control group, zinc ions can destroy the bacterial structure and induce bacterial death by inhibiting bacterial biofilm formation and interfering with amino acid metabolism and enzyme systems. 99% of Staphylococcus aureus and Escherichia coli were killed after only two hours of contact with dopamine-zinc alginate dressing APBM. Among them, DPU and ZnPU have an inhibitory effect on Staphylococcus aureus of 60% and 75%, respectively, and an inhibitory effect on Escherichia coli of 50% and 65%, respectively. However, due to the lack of chemical antibacterial properties, the inhibition rate of PU is only 8.69%. The above results show that the antibacterial effect of dopamine-zinc alginate dressing APBM is better than that of dressings with only ZnPU (active sterilization) and DPU (passive antibacterial).

[0101] To test the in vitro bacterial barrier performance of APBM, the agar diffusion experiment was used to evaluate the bacterial barrier effects of the dressings DPU, ZnPU, and APBM. PU was used as the control group. The specific method was as follows: PU, DPU, ZnPU, and APBM samples were cut into cylinders (10 mm × 10 mm × 5 mm) and sterilized under ultraviolet light for 30 minutes. Bacterial liquid (Escherichia coli and Staphylococcus aureus, 1×10 6 CFU / L, 1mL) was evenly dropped on one side of the dressing (i.e., the upper layer). The sample with the bacterial solution on the surface was placed on an LB agar plate (the surface that first contacts the bacteria faces upward) and placed in a 37°C bacterial incubator. The culture dish was taken out for daily observation to observe the changes in bacterial penetration of the dressing and the growth area. Four groups of samples were tested according to the above test method. The test results are as follows Figure 8 As shown, in the PU group, Staphylococcus aureus and Escherichia coli both grew on the plate through the dressing and had the largest area, indicating that the PU dressing had no antibacterial effect. After one week of continuous culture in the APBM group, no infection appeared on the dressing surface. However, the control dressing was covered with colony infection, and their color turned yellow, indicating that the entire dressing was infected with bacteria. It can be seen that the bacterial infection area of ​​PU, DPU (passive antibacterial) and ZnPU (active bactericidal) increased over time. Among them, the bacterial growth area of ​​the DPU group was reduced by 20% and 40% compared with the PU group, mainly because dopamine self-polymerized on the sponge surface to form a firm dark brown PDA coating. In addition to its own antibacterial effect, the rough surface facilitated bacterial adhesion to the material surface, preventing some bacteria from growing on the plate through the sponge. The area of ​​bacterial infection was calculated on the 7th day of culture. The infection area of ​​Staphylococcus aureus SA in the PU group was as high as 12cm 2 , E. coli EC infection area up to 16cm 2 No bacterial infection occurred in APBM, indicating that APBM provided a good barrier for surface bacteria, making it difficult for external bacteria to invade.

[0102] In order to explore the independent antibacterial performance of APBM, the antibacterial performance of PU, DPU and APBM dressings was tested respectively, and the antibacterial ability of APBM was quantitatively verified by bacterial capture experiment, that is, soluble hyaluronic acid filter membrane (HAFM). The test method is as follows: the dressings were cut into a cylinder with a height of 5 mm and a diameter of 10 mm, and after UV sterilization for 30 minutes, they were placed in an acrylic cylinder with a diameter of 10 mm and a height of 10 mm. A transparent air filter membrane (HAFM) with a diameter of 12 mm was placed on a clean transparent plate, and the bottom of the cylinder was in contact with the filter membrane (but not with the sponge). The aerosol bottle (containing Staphylococcus aureus liquid, 1×10 4CFU / L, 5mL) is placed over the acrylic cylinder with a nozzle that covers the sponge and is timed for 30 seconds for spraying. After the spraying is completed, let it stand for 1 minute, take out the HAFM and place it in an LB culture dish for 30 seconds, wait for the membrane to dissolve and then coat the plate. After incubation at 37°C for 24 hours, observe the colonies on the agar plate and take pictures. It should be noted that HAFM is a filter membrane with a porous structure constructed by an ethanol-induced phase separation strategy (a porous filter membrane for efficient capture and instant quantitative detection of airborne pathogens prepared in Example 1 of Patent 202410540252.7), which can capture and collect pathogens in the air with high performance. Therefore, it is extremely effective to use it to collect the close closed environment formed by the acrylic cylinder and the aerosol bottle. After spraying, let the HAFM stand and place it in an LB culture dish for coating the plate. The test results are as follows Fig. 9 The results showed that compared with the PU group, the APBM group could achieve an 80% antibacterial effect, and the antibacterial rate of the DPU group was greater than 55%, indicating that the passively designed dopamine modified layer can play a role in preventing bacterial adhesion, and the APBM has a more superior effect overall.

[0103] Biocompatibility is the basic premise for the clinical transformation of wound dressings. To test the biocompatibility of dopamine-zinc alginate dressing, we conducted cytotoxicity test and hemolysis test.

[0104] The specific method of the cytotoxicity test is as follows: the CCK-8 method is used to evaluate the cytotoxicity of the sponge. L929 cells were cultured in DMEM medium containing 10% fetal bovine serum and double antibodies. The control group was a group that only added culture medium. The dopamine-zinc alginate dressing sponge APBM prepared in Example 1 was soaked in DMEM high-glucose medium for 24 hours, and the sponge extract was obtained after filtering using a 0.22 μm filter membrane (Sartorius, Germany). Then it was diluted to 0.25, 0.5, 0.75 and 1 mg / mL. The L929 cell concentration was adjusted to 5×10 4 cells / mL, 100μL per well was inoculated in a 96-well plate, and after the cells adhered to the wall, different concentrations of sponge extract were replaced, and then 100μL of sponge extract was used to replace the culture medium and continued to culture for 24h and 72h. After the corresponding culture time, the original culture medium was aspirated, and 100μL CCK-8 detection solution (CCK-8: DMEM culture medium = 1:9) was added to each well, incubated at 37℃ for 2h, and the OD value was measured at 450nm using an enzyme marker. The calculation formula of cell proliferation rate is as follows:

[0105]

[0106] OD1 and OD0 represent the absorbance values ​​of the experimental object and the negative control, respectively.

[0107] The test results are as follows Fig.10As shown in (a), the results showed that compared with the control group, each concentration group had no effect on cell activity and there was no statistical difference.

[0108] Hemolysis experiment: The hemolysis of PU and the dopamine-zinc alginate dressing APBM prepared in Example 1 was evaluated using anticoagulated whole blood from New Zealand white rabbits. Red blood cells were obtained by centrifuging whole blood at 1500 rpm for 15 minutes and then washed in PBS until the supernatant was colorless. 1 mL of red blood cells was added to 9 mL of sterile PBS and mixed to prepare a red blood cell suspension. Subsequently, 1 mg of the sample was added to 1 mL of diluted blood as the experimental group and then diluted. The red blood cells were added to deionized water and PBS as the positive control and negative control, respectively. After incubation at 37°C for 1 hour, all groups were centrifuged at 2000 rpm for 5 minutes. The absorbance of the supernatant at 540 nm was measured using a UV-visible spectrophotometer. The hemolysis ratio (HR) of the sponge was calculated according to the following formula (5).

[0109]

[0110] OD S Indicates the absorbance of the dressing, OD (+) Indicates the absorbance of positive samples, OD (-) Indicates the absorbance of negative samples.

[0111] The test results are as follows Fig.10 As shown in (b), the hemolysis rate of wound dressings below 2% is the minimum standard for the clinical application of biomedical materials. After evaluation, the hemolysis activity test of dopamine-zinc alginate dressing APBM showed that its hemolysis rate was less than 1.5% compared with the positive group. The above results show that dopamine-zinc alginate dressing has good biocompatibility and provides a reliable basis for wound treatment.

[0112] The main difficulty in treating burn wounds is microbial infection and inflammation, which ultimately hinder wound healing. In order to explore the healing and anti-inflammatory effects of dopamine-zinc alginate dressings, the wound healing effect of burn infected wounds in rats was verified. The specific experimental methods are as follows:

[0113] In order to evaluate the bacterial barrier performance and healing performance of dopamine-zinc alginate dressing as a wound dressing, a rat bacterial infection scald model was designed. Ordinary SD rats were randomly divided into a control group, a PU group, a DPU group, and a dopamine-zinc alginate dressing group. The backs of anesthetized rats were shaved and depilatory cream was used to remove hair. The exposed skin was sterilized with 1% povidone-iodine solution and washed with normal saline. Two deep second-degree burns with a diameter of 1.5 cm were made on the back of the rat using a scald instrument. After thirty minutes, the scab part of the wound was removed, and then the dopamine-zinc alginate dressing and PU dressing were fixed on the wound surface. Subsequently, 1 mL of Staphylococcus aureus suspension (1×10 6 CFU / mL-1 ) was sprayed on the wound and dressing surface, while the control group was sprayed with bacterial liquid on the wound surface. The rats were marked and fed individually, and the wounds were photographed. The dressings were changed every 4-5 days and the recovery of the wounds was observed. ImageJ was used to analyze the wound closure area. The wound healing rate was calculated by the following formula.

[0114]

[0115] Where S0 and S represent the initial wound area and the wound area on the day of examination, respectively.

[0116] It should be noted that all experiments were performed as per the guidelines for the care and use of laboratory animals, and every effort was made to minimize suffering. This study was approved by the Animal Ethics Committee of Qingdao University, China (No.: QDU-AEC-2024708). The experimental protocol was performed in accordance with the ARRIVE guidelines. Sprague Dawley rats (male, 250-280 g, production license number: SCXK(Lu)2022-0006) were purchased from Jinan Pengyue Laboratory Animal Co., Ltd.

[0117] The results are as follows Fig.11 As shown, the blank treatment was used as a control to further evaluate the effect of APBM on the healing ability of scald infected wounds. The wound area was quantitatively analyzed on days 0, 5, 8, 11, and 15 after the wound. The wound was porcelain white with mild swelling after the scald. Then on the fifth day, the skin in the wound area began to change color and scab. The color of the skin changed from porcelain white to light yellow, brown or light brown, and finally to red and black. By the eighth day, there was a clear boundary between the scald area and the normal tissue. The wound showed tissue congestion and local brown and red borders. Compared with the other three groups (blank control group, PU, ​​DAPU), APBM sponge significantly promoted wound closure and showed a faster healing speed than the other groups. Especially in the period from day 2 to day 10. By day 15, the average wound closure rates of the blank control group, PU, ​​DPU, and APBM were 60.27%, 64.32%, 73.49%, and 87.39%, respectively; the healing speed of the wound treated with APBM was significantly faster than that of the other three groups during the 15 days of healing.

[0118] In order to comprehensively evaluate the therapeutic effect of APBM, tissue samples were subjected to histopathological evaluation, and hematoxylin and eosin (H&E) staining and Masson's trichrome staining were used to analyze the degree of inflammatory infiltration, re-epithelialization, angiogenesis, and collagen content. After surgery, the soft tissues around the wound were collected on the 11th and 15th days for histopathological analysis. In brief, the tissues were dehydrated in ethanol, cleaned in xylene, and then embedded in paraffin. H&E staining, Masson staining, and immunofluorescence staining were used to evaluate the collagen deposition, epithelialization, angiogenesis, and inflammatory infiltration of the wound surface. The blank control group was an untreated group that was only scalded but not given any medication. The test results are as follows Fig.12 As shown. By H&E staining, it was found that in the blank control group and PU group, immune cells infiltrated into the interstitial area and muscle tissue around the implant, and there was a significant accumulation of inflammatory cells and inflammatory necrosis foci on the tissue surface. The APBM group significantly inhibited neutrophil infiltration. In the process of wound healing, since epithelial cells can serve as a skin barrier to avoid pathogen infection, it is crucial to evaluate re-epithelialization for wound healing. Histological results showed that compared with the blank control group and PU group, wounds treated with DPU and APBM sponges showed re-epithelialization, especially in the central area of ​​the defect. In addition, by HE staining on days 11 and 15, it was observed that the new epidermis in the APBM group was well formed. By day 15, in the APBM group, the new epidermis was well integrated with the dermis, and relatively intact epidermis and dermis were observed. This highlights the role of APBM in the early regeneration stage that affects inflammation, proliferation, and healing. Collagen can repair defects, restore the tissue structure and function of tissues, improve the extracellular matrix skeleton, and lay the foundation for the formation of wound cell matrix. During the remodeling phase of vascular and skin healing, collagen deposition is necessary to enhance the tensile strength of tissues and support wound healing. In this study, collagen formation was observed by Masson staining. The results showed that on the 11th day, only a small amount of loose and disordered collagen fibers were present in the blank-treated group and PU-treated wounds. In contrast, on the 11th and 15th days after surgery, the skin tissue of rats in the APBM group showed denser collagen fibers and more collagen deposition. At the same time, the histological results on days 11 and 15 showed that the amount of collagen fiber deposition in the APBM group was more than 2.5 times that in the blank control group and the PU group. It was also better than the collagen deposition results of the DPU group. Collagen is denser and more mature. It has a highly ordered fibrous collagen structure, which is similar to the histopathological structure of normal skin tissue, which is beneficial to maintain the mechanical integrity of the skin and reduce scar formation. This also shows that the incorporation of zinc ions and the design of antibacterial strategies significantly enhance collagen fiber deposition.

[0119] During wound healing, neovascularization is essential to ensure adequate nutrient and oxygen delivery to wound tissue to support fibroblast proliferation, collagen synthesis, and re-epithelialization. Immunofluorescence staining of CD31 and α-smooth muscle actin (α-SMA) was performed to investigate the angiogenesis and recovery in wound tissue. Angiogenesis is required for tissue regeneration and repair. Impaired angiogenesis delays wound closure and increases the risk of infection. CD31 is a transmembrane protein expressed in angiogenesis, indicating neovascularization. The effect of APBM on CD31 expression is shown in the figure. On day 11, the expression level of CD31 in the APBM group was significantly higher than that in the blank control group and the PU group (P<0.01). On day 15, the expression trend of CD31 in the APBM group was consistent with that on day 11 (P<0.001). These studies indicate that APBM dressings can promote angiogenesis during wound healing and further accelerate wound healing. α-SMA is a cytoplasmic protein expressed in late angiogenesis, indicating the maturation of vascular smooth muscle cells. Immunofluorescence experiments showed that compared with the blank control group, PU and DPU groups, the expression of α-SMA in the APBM treatment group was significantly higher than that in the other three groups on days 11 and 15, and the fluorescence expression intensity was more than 2 times. This shows that APBM dressing can more effectively stimulate angiogenesis in wounds.

[0120] In summary, the APBM group accelerated the healing of rat burn wounds by reducing wound inflammatory infiltration, promoting re-epithelialization, collagen deposition and angiogenesis in damaged skin lesions. The above results strongly support the better application prospects and potential of APBM dressings in open wounds and infected wounds.

[0121] Although the present invention has been described in detail by combining the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. An active and passive synergistic antibacterial and healing-promoting dressing, characterized in that: The dressing is a dopamine-sodium alginate-zinc ion composite functional dressing, and the dressing is a modified hydrogel-coated polyurethane dressing synthesized by modifying dopamine and then cross-linking with sodium alginate and zinc ions.

2. The active and passive synergistic antibacterial and healing-promoting dressing according to claim 1, characterized in that: The dressing has passive adhesion and antibacterial properties and active antibacterial properties of zinc ion release; the passive antibacterial efficiency can reach 80±1.2%, and the antibacterial rate of the active and passive synergistic antibacterial and healing-promoting dressing can reach more than 99%.

3. The active and passive synergistic antibacterial and healing-promoting dressing according to claim 1, characterized in that: The dressing has mechanical properties and liquid management capabilities. The liquid absorption rate of the dressing is more than twice that of polyurethane sponge PU, and it has water absorption and water retention properties, and can effectively control wound exudate.

4. The method for preparing the active and passive synergistic antibacterial and healing-promoting dressing according to claim 1, characterized in that: The dressing uses a polyurethane sponge as a substrate, and forms a passive antibacterial layer with hydrophilicity and water absorption through in-situ polymerization of dopamine and the polyurethane sponge; and then uses sodium alginate and zinc ion solution for cyclic cross-linking treatment to form a hydrogel coating containing zinc ions to obtain a modified polyurethane dressing.

5. The method for preparing the active and passive synergistic antibacterial and healing-promoting dressing according to claim 1, characterized in that: The following steps are involved: 1) Composite of dopamine and polyurethane sponge: The polyurethane sponge is mixed with the dopamine solution and self-polymerized in an alkaline environment to form a polydopamine coating; 2) Sodium alginate-zinc ion gelation: The dopamine-modified polyurethane sponge is immersed in a sodium alginate and zinc ion solution, and is cross-linked multiple times for a short time to form a zinc-containing sodium alginate hydrogel coating; 3) freeze-drying the cross-linked dressing to obtain the active and passive synergistic antibacterial and healing-promoting dressing.

6. The method for preparing the active and passive synergistic antibacterial and healing-promoting dressing according to claim 5, characterized in that: The concentration of the dopamine solution in step 1) is 2 mg ± 0.5 mg / mL, and the alkaline environment in step 1) is tris(hydroxymethylaminomethane) hydrochloride buffer.

7. The method for preparing the active and passive synergistic antibacterial and healing-promoting dressing according to claim 5, characterized in that: In step 2), the concentration of sodium alginate is 0.01-2 g / mL, and the concentration of zinc ions is 8-40 mg / mL.

8. The method for preparing the active and passive synergistic antibacterial and healing-promoting dressing according to claim 5, characterized in that: In step 2), the time of short-term multiple cross-linking is 0.5-3 minutes, and the number of cross-linking is 2-6 times.

9. Use of the active and passive synergistic antibacterial and healing-promoting dressing as described in any one of claims 1 to 3 in the preparation of dressings related to open wounds.

Citation Information

Patent Citations

  • Chitosan-based gauze dressing loaded with metal ions and preparation method thereof

    CN109010898A

  • Porous filtering membrane for efficient capture and instant quantitative detection of air pathogens as well as preparation method and application of porous filtering membrane

    CN118491216A

  • Foam substrate dressing and preparation method thereof

    CN105536038A

  • Thermal-reversible crosslinking epoxidised natural rubber preparation method

    CN106554429A

  • Metal cation cross-linked alginate / bacterial cellulose composite hydrogel antibacterial dressing

    CN112587717A